PENGARUH PENGGUNAAN CETAKAN SPASI TERHADAP KEBUTUHAN BAHAN PADA PEKERJAAN PASANGAN BATA - Albani Musyafa (TEKNISIA, 2015)
For construction of million houses needed by Indonesians, material efficiency should be prioritized. This is because so many wasted materials in the process. For example, much mortar is wested on a masonry work. To minimize the waste, a mortar mold should be used. The objective of this study was to determine the efficiency that could be got by using a mortar mold in a masonry work. The reseach method was experiments. The result was determined by comparing the mortar needs between the two ways, i.e. with and without the masonry mold tool. Twenty-one experiments have been conducted for each way. The results of this study indicate that using of the tool could save about 23% of mortar or 23% of the material cost.